The Development of a two-tier diagnostic test for student understanding of light - Nasir, Muhammad; Cari; Sunarno, Widha; Rahmawati, Fitria (Journal of Turkish Science Education, 2024)
This study aimed to develop a two-tier light concept test to identify student concept understanding of light. The development of the test was carried out through the content validity, construct validity, and reliability test stages using the Item Response Theory (IRT). The sample consisted of 81 students during the second semester at five universities in Indonesia. The results showed that the instrument met the content validity and construct validity criteria as well as reliability. Efforts are needed to improve concepts inlight material.
Keywords: Diagnostic instrument; light concept; misconception; item response theory; certainty response index